Upaya Indonesia dalam Mengurangi Terjadinya Pelanggaran Perbatasan Maritim yang Dilakukan oleh Tiongkok di Perairan Kepulauan Natuna Tahun 2016-2017 - Rahyuda Redi, A. A. Ngurah Made; Fasisaka, Idin; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT   This research aims to describe the efforts of the Indonesian government under the leadership of Joko Widodo in reducing maritime boundary violation carried out by China in the Natuna Islands in 2016 until 2017. China claims the waters of Natuna Islands as part of its “nine-dash line”which encompasses the majority of the South China Sea, while Indonesia claims the same waters as its territory based on international law. The policies of the previous Indonesian government we re inconsistent in defend ing state ’s claims, but Joko Widodo ’s govern ance applied more assertive policies in facing the Chinese by strengthening defense and economy in affected region and actively collaborates with other nations to bolster its position. Using the concept ual framework of coercive diplomacy and balancing behavior, this research concludes that Joko Widodo ’s government applied both concept in it’s effort to reducethe violations carried out by China in the Natuna Islands.   Keywords : Indonesia, Natuna Islands, coercive diplomacy, balancing